Planning Instruction to Meet the Intent of the Next Generation Science Standards - Krajcik, Joseph; Codere, Susan; Dahsah, Chanyah; Bayer, Renee; Mun, Kongju (Journal of Science Teacher Education, 2014)
The National Research Council’s Framework for K-12 Science Education and the Next Generation Science Standards (NGSS Lead States in Next Generation Science Standards: For states, by states. The National Academies Press, Washington, 2013) move teaching away from covering many isolated facts to a focus on a smaller number of disciplinary core ideas (DCIs) and crosscutting concepts that can be used to explain phenomena and solve problems by engaging in science and engineering practices. The NGSS present standards as knowledge-in-use by expressing them as performance expectations (PEs) that integrate all three dimensions from the Framework for K-12 Science Education. This integration of core ideas, practices, and crosscutting concepts is referred to as three-dimensional learning (NRC in Division of Behavioral and Social Sciences and Education. The National Academies Press, Washington, 2014). PEs state what students can be assessed on at the end of grade level for K-5 and at the end of grade band for 6–8 and 9–12. PEs do not specify how instruction should be developed nor do they serve as objectives for individual lessons. To support students in developing proficiency in the PEs, the elements of the DCIs will need to be blended with various practices and crosscutting concepts. In this paper, we examine how to design instruction to support students in meeting a cluster or “bundle” of PEs and how to blend the three dimensions to develop lesson level PEs that can be used for guiding instruction. We provide a ten-step process and an example of that process that teachers and curriculum designers can use to design lessons that meet the intent of the Next Generation of Science Standards.